Apocalypse Never : Forging the Path to a Nuclear Weapon-Free World - Daley, Tad (Book collections on Project MUSE., 2010)
Argues that nuclear weapons pose the single most immediate peril to humans, explains that their abolition is both essential and achievable, and details what governments and individuals need to do to make this abolition a reality.